Advancing Knowledge for Use in Coastal and Estuarine Management: Competitive Research in the National Estuarine Research Reserve System. Issue 3 (4th May 2019) - Trueblood, Dwight; Almazán-Casali, Stefania; Arnott, James; Brass, Maeghan; Lemos, Maria Carmen; Matso, Kalle; Read, Jennifer; Vaccaro, Lynn; Wondolleck, Julia
Abstract: Decades of research has generated new scientific understanding and technologies aimed at better managing environmental change in estuarine and coastal regions. Yet many across the communities of coastal and estuarine research, management, and funding believe that progress has been too slow in applying this research in practice. This essay reviews how the National Estuarine Research Reserve System's funding program evolved over the past two decades to improve how researchers and users of research work together to increase the uptake of science to achieve resource management and conservation goals. Incremental innovation in the design of the NERRS funding program enabled more intensive and multiway engagement between funders, researchers, and users, which created new pathways for applying science in practice. Furthermore, these interactions stimulate reflection and adaptation within each separate institutional setting, supporting changes that may science to better support environmental problem solving.